Desempenho da membrana de ultrafiltração no pós-tratamento de efluente secundário com vistas ao reuso - Porto, Camila de Almeida (2019)
The membrane separation processes are being applied in secondary effluents to enable reuse in various modalities. The present work evaluated the performance of a pilot ultrafiltration system in the post-treatment of facultative pond effluent at Mangabeira Wastewater Treatment Plant in João Pessoa/PB. Short and long duration experiments were performed to evaluate the behavior of transmembrane pressure based on experimental planning. The feed and permeate characterization were also performed to evaluate the reuse potential. The stability of the system was observed at a relatively low filtration rate, around 32.5 L. m-2. h-1. The physical cleaning conditions did not influence the removal of the reversible fouling, indicating the possibility of reducing the rate and the rate of the backwash. The base chemical cleaning conditions had no influence on the removal of irreversible fouling, except the frequency. The in-line coagulation addition (PAC, 3 mg. L1, natural pH) was essential for the maintenance of the transmembrane pressure of the pilot plant. The feed presents a high organic load in terms of COD and turbidity, limiting the filtration rate. The permeate has a low organic load (average of 5 mg. L-1 BOD5, 26 mg. L-1 COD and 0,7 UNT turbidity), no thermotolerant coliforms and transparency, meeting different national - ABNT (1997), Estado de São Paulo (2017), Estado do Ceará (2017), Prosab (2006) - and international - the United States (2012) and Spain (2007) - reuse standards. However, an additional treatment is necessary for industrial reuse (Aquapolo Ambiental Standard).